Tinnitus in adolescents: the start of the vulnerability of the auditory pathways - Sanchez,Tanit Ganz (2015)
INTRODUCTION: Although tinnitus is an increasingly common symptom, few studies have assessed its prevalence or incidence among adolescents.PURPOSE: To assess whether the presence of tinnitus in adolescents is associated with minimal hearing damage, evaluated through high-frequency audiometry (HFA), otoacoustic emission (OAE), and loudness discomfort level (LDL).METHODS: The sample comprised 168 adolescents of a private school (61.3% boys; mean age 14.1 years old; standard deviation=2). All of them completed a questionnaire about tinnitus and hypersensitivity to sounds (sound intolerance), and then underwent otoscopy, pure-tone audiometry, HFA, LDL, transient and distortion product otoacoustic emissions (TOAE and DPOAE), and tinnitus pitch/loudness matching (the latter only in those with tinnitus). Participants were later divided into three groups: with no tinnitus (n=73, 43.4%), with sporadic tinnitus (n=47, 28%), and with constant tinnitus (n=48, 28.6%).RESULTS: No significant difference was observed between the groups regarding audiometry thresholds in frequencies from 0.25 to 16 kHz, or TOAE and DPOAE. However, the LDL in adolescents with constant tinnitus was significantly lower than that in other groups, suggesting hypersensitivity to sounds.CONCLUSION: There was no evidence of minimal hearing damage in the audiometry and OAE. Nonetheless, the decreased LDL in adolescents with constant tinnitus suggests that their auditory system is more sensitive. Therefore, this may be the first sign of vulnerability to sounds. Future medium- to long-term monitoring of these students may show whether they will begin a process of functional impairment, altering hearing thresholds, and OAE.